Special Issue of the Manufacturing Engineering Society 2019 (SIMES-2019) - Rubio, Eva M.; Camacho, Ana M. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue of the Manufacturing Engineering Society 2019 (SIMES-2019) has been launched as a joint issue of the journals Applied Sciences and Materials. The 10 contributions published in this Special Issue of Applied Sciences present cutting-edge advances in the field of manufacturing engineering, focusing on production planning, sustainability, metrology, cultural heritage, and materials processing, with experimental and numerical results. It is worth mentioning that the topic "production planning" has attracted a great number of contributions in this journal, due to their applicative approach.